Investigating Customer Satisfaction and the Elements Affecting Notebook Computer Purchases in Punjab - Singh Khehra, Kanwal Gurleen (Journal of Research in Marketing (ISSN: 2292-9355), 2020)
A laptop is a personal computer for mobile use. With the growth of personal computers in early 1980s, a need was felt to develop a computer which can be carried to mobile locations. Today it has emerged as one of the most significant tool for communication and networking and not to mention its utility for official work. The inflow of many manufacturers at considerable lower prices have made it possible in India to afford a Laptop virtually by anybody. Indian market is spread across both sides of the spectrum with large masses available at higher end and lower end with wide variety of taste and preferences. Henceforth the need arises to meet the demands and preferences of this huge market segment. This study will highlight the various factors responsible for influencing the purchase decisions of customers while buying a Notebook computer in Punjab and also an effort has been made to study the customer satisfaction level towards Notebook computers in Punjab. A sample of 200 respondents from four districts of Punjab participated in the survey. Some of the research techniques used in the study includes Factor analysis.